2017
DOI: 10.1103/physreve.95.063111
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear perturbation analysis of the symmetry breaking in time-periodic propulsive wakes

Abstract: The two-dimensional and time-periodic wake flows produced by a pitching foil are investigated numerically for a fixed flapping amplitude. As the flapping frequency is increased, three regimes are identified in the time-marching nonlinear simulations. The first regime is characterized by nondeviated wake flows with zero time-averaged lift. In the second regime, the wake flow is slightly deviated from the streamwise direction and the time-averaged lift is slightly positive or negative. The third regime is charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…For example, Williamson and Roshko (1988) and Morse and Williamson (2009) report this mode for experimental studies of the controlled oscillation of circular cylinders, and Leontini et al (2006) clearly showed this mode for the same problem numerically. Similar spatio-temporal symmetry breaking modes have been found in other oscillating body wake flows, such as flapping foils (Jallas et al, 2017). However, perhaps the most relevant is the work from Singh and Mittal (2005), who found evidence of this mode in the wake of an elastically mounted circular cylinder.…”
Section: Features Of Note For Thesupporting
confidence: 61%
“…For example, Williamson and Roshko (1988) and Morse and Williamson (2009) report this mode for experimental studies of the controlled oscillation of circular cylinders, and Leontini et al (2006) clearly showed this mode for the same problem numerically. Similar spatio-temporal symmetry breaking modes have been found in other oscillating body wake flows, such as flapping foils (Jallas et al, 2017). However, perhaps the most relevant is the work from Singh and Mittal (2005), who found evidence of this mode in the wake of an elastically mounted circular cylinder.…”
Section: Features Of Note For Thesupporting
confidence: 61%
“…The generalised eigenvalue problem (2.3) is solved by the Arnoldi method or by a simple inverse iteration algorithm. Finally, nonlinear unsteady Navier–Stokes equations are integrated forward in time with a second-order time scheme (Jallas, Marquet & Fabre 2017).…”
Section: Problem Formulation and Investigation Methodsmentioning
confidence: 99%
“…Therefore, the global analysis method must be adapted to account for this periodicity, by use of the Floquet theorem (Floquet 1883). A global Floquet formalism has been successfully applied by Barkley & Henderson (1996) to the secondary instability of a cylinder wake around Re = 200 and more recently by Jallas et al (2017) to a study of secondary instabilities in wake flows.…”
Section: Introductionmentioning
confidence: 99%